Metagenomic next-generation sequencing assists the diagnosis treatment of fungal osteoarticular infections - Zhang, Chaofan; Lin, Yunzhi; Huang, Changyu; Huang, Zida; Fang, Xinyu; Bai, Guochang; Zhang, Zeyu; Li, Wenbo; Zhang, Wenming (Frontiers in Cellular and Infection Microbiology, 2022)
Background Fungal osteoarticular infection (FOI) is not commonly seen in clinical practice but proposes a great challenge to orthopedic surgeons. In this study, we aimed to investigate the risk factors, the clinical features, and surgical outcomes of FOI in our institution. Specifically, we aimed to explore the role of metagenomic next-generation sequencing (mNGS) in the diagnosis and treatment of FOI. Methods All the patients who were diagnosed and managed with FOI in our institution from January 2007 to December 2020 were retrospectively reviewed, including primary fungal implant-related infection, primary fungal osteomyelitis or arthritis, and fungal infections secondary to bacterial osteomyelitis or implant-related bacterial infections. The potential risk factors and the clinical and surgical features were analyzed. The pathogen data were compared between culture and the mNGS test. Results A total of 25 patients were included, namely, 12 primary implant-related infections, 7 primary fungal osteomyelitis or arthritis, and 6 fungal infections secondary to bacterial osteomyelitis or implant-related bacterial infections. Most cases had undergone multiple surgeries or long-term antibiotic treatment. Diagnosis was mainly based on microbial culture and the mNGS test. Optimization of culture methods and the use of mNGS assisted the diagnosis. Specifically, mNGS was performed in 12 patients, 5 of whom were culture-negative. In the remaining seven cases, mNGS demonstrated the same results as culture. Management of FOI was complicated as most patients required multiple surgeries followed by long-term antifungal treatment. In selected cases, antifungal-impregnated cement spacer retention can be an optional choice. The overall success rate was 100% (25/25) for our cohort. Conclusion We concluded that patients with comorbidities and a history of multiple surgeries or long-term antibiotics are under higher risk for FOI. Use of mNGS assists the diagnosis and treatment of FOI. Surgery combined with long-term antifungal treatment achieved satisfactory outcomes. In selected cases, antifungal-impregnated cement spacer retention can be an optional treatment choice.